2019
DOI: 10.1111/mmi.14316
|View full text |Cite
|
Sign up to set email alerts
|

Division plane placement in pleomorphic archaea is dynamically coupled to cell shape

Abstract: Summary One mechanism for achieving accurate placement of the cell division machinery is via Turing patterns, where nonlinear molecular interactions spontaneously produce spatiotemporal concentration gradients. The resulting patterns are dictated by cell shape. For example, the Min system of Escherichia coli shows spatiotemporal oscillation between cell poles, leaving a mid‐cell zone for division. The universality of pattern‐forming mechanisms in divisome placement is currently unclear. We examined the locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
7
33
0
Order By: Relevance
“…Live imaging is essential for the understanding of complex dynamic cellular events, such as changes in cell shape, cell division and DNA segregation. Despite such methods being well-established in bacteria and eukaryotes, live imaging has only recently been applied to the study of cell biological processes in archaea [1], where imaging of halophilic archaea has led to surprising new findings [2][3][4][5]. Live imaging of archaea remains challenging, especially when compared to bacteria, because archaea tend to be mechanically soft and several representatives are extremophiles, necessitating the development of novel techniques [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Live imaging is essential for the understanding of complex dynamic cellular events, such as changes in cell shape, cell division and DNA segregation. Despite such methods being well-established in bacteria and eukaryotes, live imaging has only recently been applied to the study of cell biological processes in archaea [1], where imaging of halophilic archaea has led to surprising new findings [2][3][4][5]. Live imaging of archaea remains challenging, especially when compared to bacteria, because archaea tend to be mechanically soft and several representatives are extremophiles, necessitating the development of novel techniques [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, haloarchaea might have conserved at least two distinct elongation modes in addition to cell division, generating disk-like and rod-like populations (32). This scenario would also corroborate the morphological malleability of haloarchaea, being capable of assuming unusual shapes like triangles and squares (33,34).…”
Section: Discussionmentioning
confidence: 69%
“…Then, 10 µl of the concentrated cells was transferred to under a 0.5% agarose pad with CA medium and observed using a Nikon Eclipse TiE inverted TIRF microscope. ArtA-msfGFP time lapses were acquired by culturing H. volcanii cells inside Millipore ONIX CellAsic microfluidic plates as previously described (33). Images were taken under 5-minute intervals for 12 hours in both phase contrast and with 488 nm laser channels.…”
Section: Construction Of Expression Plasmid For Csg-msfgfp(sw) and Msmentioning
confidence: 99%
“…Movies were acquired for half an hour at one frame per 10 seconds using 100 ms exposures with 30 mW 488 nm laser illumination. Calculation of parameters of oscillation: Cell shape outlines and their respective lowest harmonic modes were detected using software available publicly on Github at: https://github.com/lilbutsa/Archaea_Division_Analysi s as described in 45 . The magnitude of oscillations were calculated by taking the inner product of the lowest harmonic mode of each cell shape with their respective fluorescent signal for each frame 73 .…”
Section: Author Contributionsmentioning
confidence: 99%
“…To assess if ParA/MinD homologs in archaea play a role in cellular positioning, we selected the model archaeon Haloferax volcanii, which has genetic tools and fluorescent fusion proteins available to address questions relating to intracellular organization. Recent work in H. volcanii has indicated that positioning of the motility structure, chemosensory arrays and cell division machinery is regulated by unknown mechanisms [43][44][45] . H. volcanii cells display different shapes dependent on the growth stage of the culture 43,44,46 .…”
Section: Introductionmentioning
confidence: 99%